DIGITAL MARKETING A CATALYST IN CREATING BRAND IMAGE THROUGH CUSTOMER - et. al., Dr.Ennala Deepa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A famous quote says “Content is fire; social media is gasoline (by Jay Baer). If the product has content and the same can be marketed through various digital sources this will enhance the sales of the company. Through digital marketing nowadays marketers are building relationships through links. This paper speaks in point by point about computerized way of promoting the development and different instruments. Contrast between conventional promoting and advanced showcasing is additionally appeared, how digital marketing can help in making brand with the assistance of different devices getting associated. Brand creation is finished remembering the client, the paper discusses different advances associated with making brand through digital marketing.